Income Convergence during the Disintegration of the World Economy, 1919-39 - Milanovic, Branko (World Bank, Washington, DC, 2014)
Some economists have argued that the process of disintegration of the world economy between the two world wars led to income divergence between the countries. This is in keeping with the view that economic integration leads to income convergence. The paper shows that the view that the period 1919-39 was associated with divergence of incomes among the rich countries is wrong. On the contrary, income convergence continued and even accelerated. Since the mid-19th century, incomes of rich countries tended to converge in peacetime regardless of whether their economies were more or less integrated. This, in turn, implies that it may not be trade and capital and labor flows that matter for income convergence but some other, less easily observable, forces like diffusion of information and technology.